2014
DOI: 10.1016/j.immuni.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Epigenetic Signatures Delineate Transcriptional Programs during Virus-Specific CD8+ T Cell Differentiation

Abstract: When this Resource was published, the accession number of the newly reported data was not included. The missing information appears in the following text, and the authors regret this oversight. ACCESSION NUMBERSThe RNA-seq and ChIP-seq data are available in the Sequence Read Archive under the accession number SRP049743.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 0 publications
5
64
0
Order By: Relevance
“…The mechanisms described here may also help to account for the origins of a class of preexisting DHSs which are present in activated T cells and recruit FOXP3 during the course of regulatory T‐cell differentiation (Samstein et al , ). Taken together, this body of evidence supports the emerging view that the critical steps in establishing immunological memory do indeed occur early during the initial stages of naïve T‐cell activation, and not during the subsequent differentiation stages when additional cell type‐specific TFs get recruited (Badovinac et al , ; Kedzierska et al , ; Russ et al , ; Crompton et al , ).…”
Section: Discussionsupporting
confidence: 71%
“…The mechanisms described here may also help to account for the origins of a class of preexisting DHSs which are present in activated T cells and recruit FOXP3 during the course of regulatory T‐cell differentiation (Samstein et al , ). Taken together, this body of evidence supports the emerging view that the critical steps in establishing immunological memory do indeed occur early during the initial stages of naïve T‐cell activation, and not during the subsequent differentiation stages when additional cell type‐specific TFs get recruited (Badovinac et al , ; Kedzierska et al , ; Russ et al , ; Crompton et al , ).…”
Section: Discussionsupporting
confidence: 71%
“…By contrast, trimethylation of lysine 27 (H3K27me3) is a correlate of transcriptional repression . Recently, it has been demonstrated that acquisition of granzyme B (GZMB) and perforin expression after naïve CD8 + T‐cell differentiation into effector CTLs was associated with enrichment at the gene promoters of histone modifications that promote gene transcription, namely H3K4me3 and H3K9Ac . Denton et al.…”
Section: Introductionmentioning
confidence: 99%
“…The development and differentiation of immune cells, as well as innate and adaptive responses, are precisely regulated and is attributed in part by dynamic epigenetic modifications (Allan and Nutt, 2014;Alvarez-Errico et al, 2014;Ansel et al, 2003;Kioussis and Georgopoulos, 2007;Russ et al, 2014;Su and Tarakhovsky, 2005;Won et al, 2014). Here we present a comprehensive review of the epigenetic dynamics related to these processes as well as the role of epigenetics in the pathogenesis of autoimmune diseases.…”
Section: Q2mentioning
confidence: 99%
“…H3K9 hyperacetylation enhances the expression of Prf1 (Perforin) and Gzmb (GranzymeB) mRNA at the Prf1 and Gzmb gene loci, which are two transcriptional target genes in CD8 + T cells (Araki et al, 2008). A recent study demonstrated that permissive histone modifications such as H3K4me3 and repressive histone modifications such as H3K27me3 at certain gene loci act on the commitment, development and differentiation of cytotoxic T cells (CTLs) (Russ et al, 2014). During naïve T cell differentiation into effector and/or memory CTLs, most of the specific gene loci eliminate the repressive H3K27me3 modification and maintain the permissive H3K4me3 regulation (Russ et al, 2014).…”
Section: T Lymphocytes and Epigenetic Modifications (Figs 3 And 4)mentioning
confidence: 99%
See 1 more Smart Citation